2022
DOI: 10.1094/pdis-12-21-2731-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pectobacterium punjabense Causing Blackleg and Soft Rot on Potato in Hebei and Fujian Province, China

Abstract: Pectobacterium spp. and Dickeya spp. cause blackleg and soft rot on potato worldwide (Charkowski, 2018). Potato plants (cv. Favorita or Jizhang 8#) with blackleg symptoms (vascular browning of crown stems, Fig. S1) were observed in the field in Zhangjiakou, Hebei province in 2018, and in Ningde, Fujian Province in 2019, in China. The disease incidence was around 50% and 10% in Zhangjiakou (5 ha) and Ningde (4 ha), respectively. Diseased plants (3 from each site) were collected to isolate the pathogen. Blackleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Potato stem rot caused by P. versatile (Han et al, 2022) and P. parvum (Wang et al, 2022a) was reported in the Fengning region in the summer of 2020; therefore, seven Pectobacterium species have been identified in potato plants in Hebei Province to date. MLSA demonstrated that a greater diversity of Pectobacterium infects potatoes at the province scale than previously reported: P. carotovorum, P. atrosepticum, P. brasiliense, P. parmentieri, P. polaris and P. punjabense in Guangdong, Inner Mongolia and Sichuan (Zhang et al, 2012;She et al, 2013;Zhao et al, 2018;Jiang et al, 2019;Cao et al, 2021;Handique et al, 2022a;Handique et al, 2022b). However, the P. carotovorum complex has been revised several times, and it is possible that some earlier isolated P. carotovorum strains might have been misclassified.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Potato stem rot caused by P. versatile (Han et al, 2022) and P. parvum (Wang et al, 2022a) was reported in the Fengning region in the summer of 2020; therefore, seven Pectobacterium species have been identified in potato plants in Hebei Province to date. MLSA demonstrated that a greater diversity of Pectobacterium infects potatoes at the province scale than previously reported: P. carotovorum, P. atrosepticum, P. brasiliense, P. parmentieri, P. polaris and P. punjabense in Guangdong, Inner Mongolia and Sichuan (Zhang et al, 2012;She et al, 2013;Zhao et al, 2018;Jiang et al, 2019;Cao et al, 2021;Handique et al, 2022a;Handique et al, 2022b). However, the P. carotovorum complex has been revised several times, and it is possible that some earlier isolated P. carotovorum strains might have been misclassified.…”
Section: Discussionmentioning
confidence: 91%
“…Blackleg and aerial stem rot of potatoes caused by SRP have become more frequent in China in recent years (Zhao et al, 2018;Cao et al, 2021;Han et al, 2022;Handique et al, 2022a;Wang et al, 2022a;Handique et al, 2022b). Potato stem rot caused by P. versatile (Han et al, 2022) and P. parvum (Wang et al, 2022a) was reported in the Fengning region in the summer of 2020; therefore, seven Pectobacterium species have been identified in potato plants in Hebei Province to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P. atrosepticum and P. carotovorum were once regarded as the most frequently isolated pathogens that are associated with potato soft rot diseases in China (Zhang et al, 2012;She et al, 2013). In recent years, other Pectobacterium species, including P. brasiliense Jiang et al, 2019), P. parmentieri (Cao et al, 2021), P. versatile (Han et al, 2022), P. polaris (Handique et al, 2022a) and P. punjabense (Handique et al, 2022b), have also been reported in the primary potato growing areas in China. Two citrate negative isolates of P. polaris were reported to cause aerial stem rot in Hebei Province, and subsequent genome-based analysis confirmed that they belonged to the newly established species, P. parvum (Wang et al, 2022a;Wang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%